EXPOSURE OF A SERVICE TECHNICIAN REPAIRING A BIPLANE X-RAY SYSTEM. Issue 1 (5th September 2018) - Elmiger, R; Schanz, U; Ott, B; Frei, D
Abstract: While repairing a biplane cardiovascular X-ray system in a hospital, a service technician accidentally activated the system's floor pedal. He continued his work under unnoticed exposure for about 5 min until the system alarm was automatically activated. About 2 h after the exposure, the technician developed an erythema on parts of his left face and neck. The next day, he reported his incident to the competent authorities and was hospitalised in a unit specialised in treating heavily irradiated patients. Frequent blood analysis did not show any signs for a significant exposure to radiation. The Federal Office of Public Health then conducted extensive dose estimations. It could be shown that the dismounted collimator was always in front of the lateral X-ray tube, shielding the technician from the direct beam. The dose estimations came to the following conservative results: an effective dose of 5 mSv, a skin dose of 200 mSv, an eye lens dose of 100 mSv and an extremity dose (arm) of 700 mSv. The cause of the erythema remains unclear since the estimated doses are thought to be too low to induce any visible effect on the skin.